36. INITIAL COMPREHENSIVE GERIATRIC ASSESSMENT OF ELDERLY INPATIENTS AT THE DEPARTMENT OF CARDIOLOGY, THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To survey disease patterns and comprehensive geriatric assessment in the elderly at the Department of Cardiology.Method: Cross-sectional descriptive study on elderly patients treated at the Department of Cardiology, Thong Nhat Hospital.Results: The study included 185 elderly patients. Common co-morbidities include hypertension (88,6%), dyslipidemia (92,4%), ischemic heart disease (43,2%) and type 2 diabetes (27,6%). The most common geriatric problem is IADL dependence (instrumentalactivities of daily living) with 47,6%. The female group has a rate of impairment in instrumentelactivities of daily living and rate of frailty was significantly higher in the male group. Females also have higher rates of decline in life activities, malnutrition, depression and dementia, but this is not statistically significant.Conclusion: In elderly patients at the Department of Cardiology, the most common geriatric problem is IADL dependence. Women have more geriatric problems than men. Comprehensive geriatric assessment is essential in the examination and treatment of elderly patients.
Keywords: cardiovascular disease; elderly patient; comprehensive geriatric assessment